Pater and the Lacedaemonian Ideal - John Coates (Cahiers Victoriens et Edouardiens)
In his neglected essay ‘Lacedaemon’, Pater offers an account of ancient Sparta which draws parallels between the training of Sparta youth and the nineteenth century public schools. The piece epitomises the subtlety of Pater’s prose technique and his handling of ideas. While sympathising with, and even celebrating, aspects of ancient Sparta life and their Victorian analogues, he demurs from them and nudges his readers into doubts about both.